The Photovoltaic Facade and its Impact on the Energy Economy of Buildings Located in Semi-arid Areas - Youcef Kamal; Merad Yacine; Qaoud Rami (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This article presents the application of a complete methodology to predict the photovoltaic potential using solar panels on the facades of residential buildings in Biskra (Algeria). A theoretical study conducted on a representative urban residential area in Biskra as an example of the applicability of the methodology.It is based on the determination of the PV installations for the typical facade of the buildings, taking into account the architectural and technical aspects, the solar radiation on each facade is calculated by simulating the path of the sun throughout the year.The proposed solutions are then evaluated using a dynamic energy simulation to determine the most efficient ones, resulting in the potential to exploit PV and solar energy generation. The finding is the gap between the architectural availability and the overall solar suitability of the facade surfaces, and this difference is based on the following main factors: the high density of the built environment composed of high-rise street canyons and aspect ratio, the changing direction of buildings, and finally classified buildings, with complex geometry. The aim of this work is to discuss the potential of facades and other vertical elements for the photovoltaic potential of solar panels on buildings located in semi-arid regions.